mplementation of lean manufacturing to enhance the efficiency of acrylic resins production process - Sahrupi Sahrupi; Gerry Anugrah Dwiputra; Uswatun Chasanah (Universitas Serang Raya, 2020)
High lead time processing of acrylic resins leads to the production of products to consumer undergoes and high-production costs. This study aims to reduce lead time by analyzing various activities that have value-added, non-value-added, and necessary non-value-added. The research is conducted using lean manufacturing approaches on acrylic resin production processes. The analysis shows that the activity of delay and transportation is a contributor of waste that occurs in the production process of acrylic resins. Improvements by minimizing both activities in the are thining tank, reactor, and monomer tank can increase the efficiency of the production process. The improvement results show a decrease in lead time from 1298 minutes to 1075 minutes. This study demonstrates that lean manufacturing can improve the time process efficiency of 17.18%, which means the output ratio will increase by around 17.18% in a process.